Super-Resolution Imaging With Lanthanide Luminescent Nanocrystals: Progress and Prospect - Zhang, Hongxin; Zhao, Mengyao; Ábrahám, István M.; Zhang, Fan (Frontiers in Bioengineering and Biotechnology, 2021)
Stimulated emission depletion (STED) nanoscopy has overcome a serious diffraction barrier on optical resolution and facilitated new discoveries on detailed nanostructures in cell biology. Traditional fluorescence probes employed in the super-resolution imaging approach include organic dyes and fluorescent proteins. However, some limitations of these probes, such as photo-bleaching, short emission wavelengths and high saturation intensity, still hamper the promotion of optical resolution and bio-applications. Recently, lanthanide luminescent probes with unique optical properties of non-photobleaching and sharp emissions have been applied in super-resolution imaging. In this mini-review, we will introduce several different mechanisms for lanthanide ions to achieve super-resolution imaging based on STED-like set-up. Then several lanthanide ions used in super-resolution imaging will be detailedly described and discussed. Last but not least, we will emphasize the future challenges and outlook in hope of advancing next-generation lanthanide fluorescent probes for super-resolution optical imaging.